2014
DOI: 10.2337/db14-0066
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Phosphatase 3 (MKP-3)–Deficient Mice Are Resistant to Diet-Induced Obesity

Abstract: Mitogen-activated protein kinase phosphatase 3 (MKP-3) is a negative regulator of extracellular signal–related kinase signaling. Our laboratory recently demonstrated that MKP-3 plays an important role in obesity-related hyperglycemia by promoting hepatic glucose output. This study shows that MKP-3 deficiency attenuates body weight gain induced by a high-fat diet (HFD) and protects mice from developing obesity-related hepatosteatosis. Triglyceride (TG) contents are dramatically decreased in the liver of MKP-3−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 31 publications
2
43
2
Order By: Relevance
“…MKP-3 inhibition is capable of facilitating energy expenditure, peripheral glucose disposal, and insulin signaling in association with phosphorylation of HDAC 1 on serine 393 and HDAC2 on serine 394. HDAC1/2 is increased in livers of MKP-3 knockout mice fed a high fat diet to mediate the MKP-3 inhibition-offered metabolic benefits (Feng et al, 2014). These observations are in line with the downregulated transcript levels of HDAC2 and cardiac α-actin in murine hearts following a two-week Western diet feeding.…”
Section: Role Of Histone Modification In Obesogenesis and Cardiomyopathymentioning
confidence: 64%
“…MKP-3 inhibition is capable of facilitating energy expenditure, peripheral glucose disposal, and insulin signaling in association with phosphorylation of HDAC 1 on serine 393 and HDAC2 on serine 394. HDAC1/2 is increased in livers of MKP-3 knockout mice fed a high fat diet to mediate the MKP-3 inhibition-offered metabolic benefits (Feng et al, 2014). These observations are in line with the downregulated transcript levels of HDAC2 and cardiac α-actin in murine hearts following a two-week Western diet feeding.…”
Section: Role Of Histone Modification In Obesogenesis and Cardiomyopathymentioning
confidence: 64%
“…Consistent with this, high-fat diet fed MKP-3-deficient mice exhibited fasting blood glucose and fasting plasma insulin concentrations that were significantly lower in MKP-3 knockout mice compared with wild-type mice [53]. The livers of MKP-3 deficient mice were also protected from the development of hepatosteatosis [53]. These studies are provocative as they suggest a potential role for a non-MAPK substrate for MKP-3 in metabolism.…”
Section: Erk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 82%
“…This raises the possibility that MKP-3 indirectly regulates FOXO1 via ERK1/2 in the control of hepatic gluconeogenesis. In subsequent studies using a diet-induced obesity model, Feng et al utilized MKP-3-deficient mice and showed that these mice were resistant to diet-induced obesity [53]. Consistent with this, high-fat diet fed MKP-3-deficient mice exhibited fasting blood glucose and fasting plasma insulin concentrations that were significantly lower in MKP-3 knockout mice compared with wild-type mice [53].…”
Section: Erk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 98%
See 1 more Smart Citation
“…From the measurement of VO 2 and VCO 2 , the respiratory exchange ratio (RER) can be calculated to assess energy fuel utilization and energy expenditure (Evan et al , 2012). Previously, indirect calorimeter has been widely used in metabolic disease research in mice to reveal the potential roles of specific genes or treatments in regulating energy metabolism (for example: Bi et al , 2014; Feng et al , 2014). Here, we described a protocol to evaluate the resting energy metabolism of C57BL/6 mice during dark and light cycles using the Oxymax Open Circuit indirect calorimeter.…”
mentioning
confidence: 99%